2020
DOI: 10.1136/annrheumdis-2020-218467
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 receptor inhibition in primary Sjögren syndrome: a multicentre double-blind randomised placebo-controlled trial

Abstract: ObjectivesNo immunomodulatory drug has been approved for primary Sjögren’s syndrome, a systemic autoimmune disease affecting 0.1% of the population. To demonstrate the efficacy of targeting interleukin 6 receptor in patients with Sjögren’s syndrome-related systemic complications.MethodsMulticentre double-blind randomised placebo-controlled trial between 24 July 2013 and 16 July 2018, with a follow-up of 44 weeks, involving 17 referral centres. Inclusion criteria were primary Sjögren’s syndrome according to Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…Regarding IL-6 inhibition, as the IL-6 signaling is important for the IL-17 cells differentiation, an effect of tocilizumab on Th17 cells is probable. However, the results of a randomized placebo-controlled study showed that Tocilizumab had no impact on the main symptoms of SS, although improvements in joint involvement were observed ( 239 ).…”
Section: Reviewmentioning
confidence: 99%
“…Regarding IL-6 inhibition, as the IL-6 signaling is important for the IL-17 cells differentiation, an effect of tocilizumab on Th17 cells is probable. However, the results of a randomized placebo-controlled study showed that Tocilizumab had no impact on the main symptoms of SS, although improvements in joint involvement were observed ( 239 ).…”
Section: Reviewmentioning
confidence: 99%
“…10 Since with a composite endpoint response needs to be achieved on multiple items, placebo response is expected to be lower, which is crucial to demonstrate treatment efficacy. In the tocilizumab RCT of Felten et al, 1 ESSDAI response rates were 53% in the tocilizumab and 64% in the placebo group. Clinical, patient-reported, gland-centred and immunological outcomes showed negative results, suggesting no beneficial treatment effect from tocilizumab.…”
mentioning
confidence: 93%
“…We read with interest the correspondence related to the article 'Interleukin 6 receptor inhibition in primary Sjögren syndrome: a multicentre double-blind randomised placebo-controlled trial' in which possible explanations for negative findings in recent phase III randomised controlled trials (RCTs) for primary Sjögren's syndrome (pSS) are discussed, including the RCT with tocilizumab. [1][2][3] This is an important issue to raise, since there is still an unmet need for effective treatment in pSS.…”
mentioning
confidence: 99%
“…The heterogeneous presentations of patients with pSS can make the disease difficult to diagnose and treat. There are currently no available immunomodulatory therapies that have proven efficacy in targeting the underlying pathway(s) of pSS [22] with neither conventional standard nor biologic disease-modifying antirheumatic drugs demonstrating robust or substantial efficacy in large studies [11,[23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%